Daya Terima Nugget Ayam Berbasis Daun Kelor dan Tepung Kedelai - Annisa Mutiara Putri; Afriyana Siregar; Ahmad Sadiq; Muzakar Muzakar; Susyani Susyani (Nutrition Department, Poltekkes Kemenkes Tanjung Karang, 2026)
The prevalence of undernutrition among elementary school children in Indonesia is showing an increasing trend and is closely related to unbalanced eating patterns, particularly low intake of energy and protein. A diet that does not meet children's daily nutritional needs can lead to impaired growth and development, decreased academic performance, and weakened immunity. Therefore, improving dietary intake with foods high in energy and protein is one of the key strategies in addressing undernutrition in school-aged children. Nuggets made from processed chicken meat combined with moringa leaves and soybean flour are a potential alternative as snacks or side dishes that are rich in energy and protein. This study aims to determine the acceptability and nutritional content (proximate analysis) of chicken nuggets based on moringa leaves and soybean flour through organoleptic testing.The research used a completely randomized design (CRD) with four formulations tested by 30 panelists. The parameters assessed included color, aroma, taste, and texture using a 5-point hedonic scale. Data were analyzed using the Kruskal-Wallis test followed by the Mann-Whitney test, while proximate analysis was conducted in an accredited laboratory. The results showed that formulation F2 (50 grams of moringa leaves and 50 grams of soybean flour) was the most preferred by panelists in terms of color, aroma, taste, and texture. The nutritional content per 110 grams of nugget was 15,404 kcal of energy, 17.41 grams of protein, 2.42 grams of fat, and 15.64 grams of carbohydrates.